Linear-Rotary Position Control System With Enhanced Disturbance Rejection for a Novel Total Artificial Heart - Rosario V. Giuffrida; Andreas Horat; Dominik Bortis; Tim Bierewirtz; Krishnaraj Narayanaswamy; Marcus Granegger; Johann W. Kolar (IEEE Open Journal of the Industrial Electronics Society)
A novel implantable total artificial heart, hereinafter referred to as the ShuttlePump, is currently under development in a research collaboration between the Medical University of Vienna, the Power Electronic Systems Laboratory of ETH Zurich and Charite Berlin. Its novel, low-complexity, pulsatile pumping principle requires a specially shaped piston performing a controlled, synchronized linear-rotary motion while providing the necessary hydraulic force and torque. The machine design of the Permanent Magnet Synchronous Machine (PMSM)-based linear-rotary actuator was conducted in previous work of the authors, leading to the construction of a hardware prototype satisfying the application requirements in terms of electromechanical force, torque, power losses, and volume. This article provides the details of the closed-loop linear-rotary position control system required to operate the ShuttlePump. The design of the position control system targets tight reference tracking ( $±$ 8 mm linear stroke and continuous rotation) up to an operational frequency of 5 Hz, under the heavy disturbance introduced by the axial hydraulic load force, as high as 45 N. The experimental measurements show successful linear-rotary position tracking under the specified axial load, with a maximum error of 1 mm and 5 $^{° }$ .